A comprehensive discharge planning program on fatigue and functional status of patients with hepatocellular carcinoma undergoing transarterial chemoembolization: A randomized clinical controlled trial - Nawiya Yenjai; Usavadee Asdornwised; Kessiri Wongkongkam; Nutcha Pinjaroen (Belitung Raya Foundation, Indonesia, 2022)
Background: Post transarterial chemoembolization (post-TACE) causes side effects that impact patients, which leads to fatigue symptoms and reduced functional status. However, unrelieved fatigue and reduced functional status may cause patients to withdraw from treatment and negatively affect their lives. Unfortunately, the patients post-TACE only receive routine medical care at the hospital but no follow-up and continuity of care back home. Therefore, comprehensive discharge planning for these problems is necessary. Objective: This study examined the effectiveness of the comprehensive discharge planning program on fatigue and functional status of patients with hepatocellular carcinoma undergoing transarterial chemoembolization. Methods: A randomized clinical controlled trial was used. Fifty-two patients who met the study criteria were randomly assigned to an experimental group (n = 26) receiving the comprehensive discharge planning plus routine care and a control group (n = 26) receiving routine care only. The discharge planning program was developed based on the Transitional Care Model. A demographic and health data questionnaire, Fatigue Severity Scale (FSS), and Enforced Social Dependency Scale (ESDS) were used for data collection. Chi-square, Fisher’s exact, Wilcoxon signed-rank, and Mann-Whitney U tests were used for data analysis. Results: The mean scores for fatigue at 30 days after treatment between the experimental and control groups were significantly different (p = 0.003). The mean scores for the fatigue symptoms in the experimental and control groups were 1.27 ± 0.58 and 1.77 ± 0.85, respectively. The functional status from Day 7 to Day 14 after transarterial chemoembolization was different (p = 0.020). In addition, the mean scores for functional status between the experimental and control groups were significantly different (p = 0.020). On Day 14, after transarterial chemoembolization, the experimental group had an increased score in functional status from Day 7 over the scores for those in the control group. Conclusion: The comprehensive discharge planning program effectively reduces fatigue symptoms and enhances the functional status in patients with hepatocellular carcinoma undergoing transarterial chemoembolization. Therefore, the comprehensive discharge planning program can be used by nurses and multidisciplinary teams in order to achieve the effectiveness of nursing care for patients.